2000
DOI: 10.1086/302824
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the Netherton Syndrome Gene to Chromosome 5q32, by Linkage Analysis and Homozygosity Mapping

Abstract: Netherton syndrome (NS [MIM 256500]) is a rare and severe autosomal recessive disorder characterized by congenital ichthyosis, a specific hair-shaft defect (trichorrhexis invaginata), and atopic manifestations. Infants with this syndrome often fail to thrive; life-threatening complications result in high postnatal mortality. We report the assignment of the NS gene to chromosome 5q32, by linkage analysis and homozygosity mapping in 20 families affected with NS. Significant evidence for linkage (maximum multipoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(79 citation statements)
references
References 35 publications
1
74
0
4
Order By: Relevance
“…23 Mutations and polymorphisms of the protease inhibitor SPINK5 are associated with Netherton syndrome and atopy characterized by a dysregulated Th2 response and elevated IgE levels indicating a T-cell regulatory function. 24,33 SORL1 is a novel sorting receptor that regulates trafficking and processing of the amyloid precursor protein (APP). 34 Blocking APP in metastatic malignant melanoma impairs the proliferation of melanoma cells and leads to their terminal differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…23 Mutations and polymorphisms of the protease inhibitor SPINK5 are associated with Netherton syndrome and atopy characterized by a dysregulated Th2 response and elevated IgE levels indicating a T-cell regulatory function. 24,33 SORL1 is a novel sorting receptor that regulates trafficking and processing of the amyloid precursor protein (APP). 34 Blocking APP in metastatic malignant melanoma impairs the proliferation of melanoma cells and leads to their terminal differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…There are some articles about prenatal diagnosis of C-NS with amniocentesis or chorionic villus sampling in literature [21,32,33]. This study is first report of ICSI pregnancy with PGD in C-NS.…”
Section: Discussionmentioning
confidence: 78%
“…The recent identification of the defective gene in C-NS made DNA-based prenatal diagnosis possible [21]. SPINK5 (serin protease inhibitor Kazal-type 5) encodes the Kazal-type serin protease inhibitor domains.…”
Section: Discussionmentioning
confidence: 99%
“…Using these sibships in a genome-wide linkage-screen, NS was mapped to a 4 cM interval on chromosome 5q32 (135). Evaluation of candidate genes within this region revealed that NS is caused by mutations in the serine protease inhibitor gene SPINK5 (136).…”
Section: The Coml-netherton Syndromementioning
confidence: 99%